Japansk trädgårdsdesign i Sverige - Düring, Keiko (2008)
This is a BA thesis in landscape planning at the Swedish University of Agricultural Sciences in Alnarp. The purpose of the thesis is to investigate why Japanese gardens, created in Sweden, often lack the feeling connected with Japanese gardens.